(untitled) - Mahani Mahadi; Nadra Abdul Rahman; Deebaneesan Viswanathan; Izatus Shima Taib; Adnan Sulong; Waheedah Abdul Hakeem; Masro Mohamad; Imtiaz Khalid Mohammed; Ismin Izwani Zainol Abidin; Shamima Abdul Rahman; Zauyah Yusuf (Faculty of Pharmacy, Cairo University, 2016)
The demand of herbal medicine has been increasing for the purpose of reducing the side effects of modern medicine. Melicope ptelefolia (M. ptelefolia) is a local Malaysian plant claimed to have many benefits for health. This study was performed to evaluate the potential of M. ptelefolia root extract as anti-nociceptive and anti-inflammatory agents in rats. The anti-nociceptive activity of M. ptelefolia root extracts (50 and 100 mg/kg) was evaluated using acetic acid-induced writhing and tail immersion test, while the anti-inflammatory activity was studied using carrageenan-induced paw edema test. M. ptelefolia root extract significantly inhibited the pain stimulant in acetic acid-induced writhing test, however it did not exert any significant change in the tail immersion test. Nevertheless, the mean reaction time in tail immersion test of M. ptelefolia root extract increased as the doses of extract increased. Furthermore, M. ptelefolia root extract at both doses showed significant anti-inflammatory activity by reducing paw edema volume (p < 0.05). In conclusion, methanol root extract of M. ptelefolia possesses anti-inflammatory effects and anti-nociceptive effects in rats.